2001
DOI: 10.3402/fnr.v45i0.1791
|View full text |Cite
|
Sign up to set email alerts
|

The impact of child-targeted dietary counseling of parents on food (milk) preferences of preschool-aged children in the STRIP project

Abstract: Objective:To evaluate the food choices of the 6.5-year-old children in the STRIP trial. Design: 6.5-year-old children (n=102) were randomly selected for this study from participants (n=1062) in the Special Turku Coronary Risk Factor Intervention Project (STRIP), which began at the child's age of 6 months and is a prospective long-term coronary heart disease prevention trial. The children and their families (n=1054) were randomized in the main project to form an intervention and a control group. The interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This study shows that in spite of a child-targeted, repeated nutrition counselling given to the parents during the previous 6.5 y, children's nutrition knowledge and ability to explain choices in nutrition knowledge test differed only slightly between the intervention children and the control children at the age of 7 y. Indeed, this was rather unexpected, as we have previously shown that the intervention children had low saturated fat, high unsaturated fat foods readily available at home (Lagström et al, 2001;Räsänen et al, 2001), and they also had lower saturated fat and cholesterol intake (Lagström et al, 1997) and lower serum cholesterol concentrations than the control children throughout the first years of life (Niinikoski et al, 1996;Cullen et al, 2000). Also the intervention mothers have probably been excellent role models in food selection for their children.…”
Section: Discussionmentioning
confidence: 45%
“…This study shows that in spite of a child-targeted, repeated nutrition counselling given to the parents during the previous 6.5 y, children's nutrition knowledge and ability to explain choices in nutrition knowledge test differed only slightly between the intervention children and the control children at the age of 7 y. Indeed, this was rather unexpected, as we have previously shown that the intervention children had low saturated fat, high unsaturated fat foods readily available at home (Lagström et al, 2001;Räsänen et al, 2001), and they also had lower saturated fat and cholesterol intake (Lagström et al, 1997) and lower serum cholesterol concentrations than the control children throughout the first years of life (Niinikoski et al, 1996;Cullen et al, 2000). Also the intervention mothers have probably been excellent role models in food selection for their children.…”
Section: Discussionmentioning
confidence: 45%